Education: "ser" and "quehacer" of the National Reality Seminars of the University of Costa Rica - Castillo Gaitán, Bernardo (2022)
The text offers to the university's community of the University of Costa Rica a summary of "ser" and "quehacer" of the National Reality Seminars to reflect and guide both students and teachers on this topic. It is stated that the purpose of these courses is to educate based on the nine problem areas that are considered as components of reality of which synthesis is presented. It is explained that the National Reality Seminars are part of the humanist formation of the General Studies that integrate the three essential actions of the University of Costa Rica: teaching, research and social action. It is concluded that in the courses of Reality Seminars I and II the students analyze in depth the reality of the country to respond and propose scientific, viable, and committed solutions with the communities